CRITICAL THINKING SKILLS OF NATURAL SCIENCE UNDERGRADUATE STUDENTS ON BIOLOGY SUBJECT: GENDER PERSPECTIVE - Hayati, Nur; Berlianti, Nindha Ayu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
One of the most important skills needed to face the 21st-century challenges is critical thinking. Gender differences are considered to contribute to the critical thinking skills. The objective of this study was to determine students' critical thinking skills based on gender. This quantitative research involved 57 students of the Natural Sciences Education Study Program, Universitas Hasyim Asy?ari. The instrument employed was critical thinking skills test. The data was analyzed using independent samples t-test. The results showed that the average scores of critical thinking skills of male and female students were 2.60 and 2.99 respectively. In addition, there was significant difference of students? critical thinking skills between male and female [t (55) = 2.065, p = 0.044]. In conclusion, female students tend to have the higher critical thinking skills than the male.